Implementasi Kebijakan Pengadaan Barang Dan Jasa Secara Elektronik (E-Tendering) - Dewantoro, Prastyanto Budi; Maheri Laksono, Sonny Subroto (Universitas Islam Kadiri, 2026)
This study examines the implementation of the electronic procurement (e-tendering) policy in the Regional Procurement Unit (UKPBJ) of Kediri Regency, which aims to promote transparency, efficiency, and accountability in public procurement. The rapid development of information and communication technology has driven the transformation of government bureaucracy toward digital governance. The research employed a descriptive qualitative method to analyze how e-tendering is implemented, the challenges encountered, and the strategies to enhance system effectiveness. Data were collected through interviews, observations, and documentation involving officials, procurement staff, and external stakeholders. The findings reveal that e-tendering in Kediri Regency has significantly improved administrative efficiency, reduced tender delays, and increased public trust in procurement transparency. However, some challenges remain, including limited technical capacity among staff, inadequate IT infrastructure, and inconsistent interdepartmental coordination. These issues hinder optimal policy execution despite strong regulatory support. The study concludes that the success of e-tendering depends not only on technological readiness but also on human resource competence and institutional commitment. Strengthening digital literacy, improving infrastructure, and fostering interagency collaboration are crucial for achieving a fully transparent and efficient procurement system.